Self-Assembled Nanoparticles of Silicon (IV)-NO Donor Phthalocyanine Conjugate for Tumor Photodynamic Therapy in Red Light - Kadireya Aikelamu; Jingya Bai; Qian Zhang; Jiamin Huang; Mei Wang; Chunhong Zhong (MDPI AG, 2024)
The combination of photodynamic therapy (PDT) and pneumatotherapy is emerging as one of the most effective strategies for increasing cancer treatment efficacy while minimizing side effects. Photodynamic forces affect nitric oxide (NO) levels as activated photosensitizers produce NO, and NO levels in the tumor and microenvironment directly impact tumor cell responsiveness to PDT. In this paper, 3-benzenesulfonyl-4-(1-hydroxy ether)-1,2,5-oxadiazole-2-oxide NO donor-silicon phthalocyanine coupling (SiPc-NO) was designed and prepared into self-assembled nanoparticles (SiPc-NO@NPs) by precipitation method. By further introducing arginyl-glycyl-aspartic acid (RGD) on the surface of nanoparticles, NO-photosensitizer delivery systems (SiPc-NO@RGD NPs) with photo-responsive and tumor-targeting properties were finally prepared and preliminarily evaluated in terms of their formulation properties, NO release, and photosensitizing effects. Furthermore, high reactive oxygen species (ROS) generation efficiency and high PDT efficiency in two breast cancer cell lines (human MCF-7 and mouse 4T1) under irradiation were also demonstrated. The novel SiPc-NO@RGD NPs show great potential for application in NO delivery and two-photon bioimaging-guided photodynamic tumor therapy.